2021
DOI: 10.1111/1462-2920.15485
|View full text |Cite
|
Sign up to set email alerts
|

Subzero, saline incubations of Colwellia psychrerythraea reveal strategies and biomarkers for sustained life in extreme icy environments

Abstract: Colwellia psychrerythraea is a marine psychrophilic bacterium known for its remarkable ability to maintain activity during long-term exposure to extreme subzero temperatures and correspondingly high salinities in sea ice. These microorganisms must have adaptations to both high salinity and low temperature to survive, be metabolically active, or grow in the ice. Here, we report on an experimental design that allowed us to monitor culturability, cell abundance, activity and proteomic signatures of C. psychreryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 160 publications
(236 reference statements)
0
14
0
Order By: Relevance
“…The top ve downregulated genes were hC, hD, gH, iS and iE, encoding proteins FlhC, FlhD, FlgH, FliS and FliE respectively. FlhCD is a transcription activator responsible for the transcriptional activation of gene iA and involved in the regulation of the agella synthesis (Mudge et al 2021;Fitzgerald et al 2014). FlgH is the component of the L-ring located on the outer membrane layer, forming a molecular tube with the Pring (Akiba et al 1991;Minamino et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The top ve downregulated genes were hC, hD, gH, iS and iE, encoding proteins FlhC, FlhD, FlgH, FliS and FliE respectively. FlhCD is a transcription activator responsible for the transcriptional activation of gene iA and involved in the regulation of the agella synthesis (Mudge et al 2021;Fitzgerald et al 2014). FlgH is the component of the L-ring located on the outer membrane layer, forming a molecular tube with the Pring (Akiba et al 1991;Minamino et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…and at temperatures as low as −12 C. As such, and because its genome and many unusual biochemical features are already known, C. psychrerythraea has risen to become a model marine psychrophile for the study of carbon cycling in cold marine sediments, and a relevant subject for assessing growth and survivability under simulated Martian conditions. Using radiotracer methods, previous studies of this bacterium revealed protein synthesis in unamended cell suspensions at −20 C and in those supplemented with additional extracellular polymeric substances at −80 C. Mudge et al (2021) now utilize proteomic tools to reveal metabolic pathway-specific proteins produced by C. psychrerythraea in response to variations in temperature, salinity and nutrient status. In addition, useful new tools emerge from their research including a novel approach for life detection that identifies over 500 very short peptides whose sequences could be determined by either lander-based or in-orbit mass spectrometers and used as potential biosignatures of cold-or hypersaline metabolisms.…”
Section: 'Ecophysiology Of Extremophiles' Special Issuementioning
confidence: 99%
“…This indicates that extreme cold is not an insurmountable barrier for terrestrial (and presumably extraterrestrial) life. The special issue article by Mudge et al (2021) probes physiological features of Colwellia psychrerythraea, a polyextremophilic bacterium isolated from subzero marine sediments that can grow at a salinity up to 18% (wt./vol.) and at temperatures as low as −12 C. As such, and because its genome and many unusual biochemical features are already known, C. psychrerythraea has risen to become a model marine psychrophile for the study of carbon cycling in cold marine sediments, and a relevant subject for assessing growth and survivability under simulated Martian conditions.…”
Section: 'Ecophysiology Of Extremophiles' Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that factors such as surface adhesion, salinity, the segregation of impurities of all types from the ice lattice, among other factors [67,69,71,72], make our treatment of chemotaxis a simplified starting point. However, field samples and laboratory experiments have shown that cell motility is influenced by chemotaxis at low temperature [40,73,74]. Thus, although there are many complicated interactions that provide scope for future work, the basic role of chemotaxis in the distribution of biota in ice must start with a self-consistent framework, which is the focus of our work.…”
Section: Introductionmentioning
confidence: 99%